Pengaruh Kepemimpinan Transformasional, Disiplin Kerja, dan Lingkungan Kerja terhadap Kinerja ASN di Bawaslu Kabupaten Pesawaran - M. Fadhil Yanuar; Defrizal Defrizal (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The performance of civil servants is a key determinant of the effectiveness and success of public sector organizations in carrying out their duties and functions. In election supervisory institutions such as the Election Supervisory Board (Bawaslu), civil servant performance plays a crucial role due to the complexity of tasks, high demands for professionalism, and work pressures that arise throughout the electoral process. In practice, civil servant performance is influenced not only by individual capabilities but also by organizational factors that shape employees’ attitudes and work behavior. Several organizational factors are assumed to influence civil servant performance, including transformational leadership, work discipline, and the work environment. Transformational leadership emphasizes the ability of leaders to provide role models, motivate, and inspire subordinates to perform optimally. Work discipline reflects the level of compliance of civil servants with applicable rules, procedures, and work standards. Meanwhile, a safe, comfortable, and conducive work environment is believed to create working conditions that support employee morale and productivity. This study aims to analyze the influence of transformational leadership, work discipline, and the work environment on the performance of civil servants at the Election Supervisory Board of Pesawaran Regency, both partially and simultaneously. This research is expected to provide empirical insights into organizational factors that contribute to improving civil servant performance in regional election supervisory institutions. This research employed a quantitative approach with an explanatory research design. The population and sample consisted of all civil servants at the Election Supervisory Board of Pesawaran Regency, totaling 18 respondents, selected using a saturated sampling technique. Data were collected through structured questionnaires using a Likert scale. Data analysis was conducted using multiple linear regression with the assistance of the Statistical Package for the Social Sciences (SPSS). Prior to regression analysis, the data were tested for validity, reliability, and classical assumptions to ensure the adequacy of the research model. The results indicate that, partially, transformational leadership does not have a significant effect on civil servant performance. In contrast, work discipline and the work environment have a positive and significant effect on performance. Simultaneously, transformational leadership, work discipline, and the work environment have a significant influence on civil servant performance at the Election Supervisory Board of Pesawaran Regency. Based on these findings, it can be concluded that improving civil servant performance in the Election Supervisory Board of Pesawaran Regency is more effectively achieved through strengthening work discipline and creating a safe, comfortable, and conducive work environment.